Mud volcanoes in the Khar Argalantyn Nuruu, NW Gobi Altay, Mongolia as manifestation of recent seismic activity - Rukavickova,L.; Hanzl,P. (Journal of Geosciences, 2008)
A group of mud volcanoes was discovered in the NW part of the Gobi Altay on a northern foothill of the Khar Argalantyn Nuruu Mts. Several mud cones and mud mounds with elevation up to 0.8 m, as well as pools with muddy water and mud outflows were encountered. Jurassic to Quaternary sedimentary successions provide the source for the mud volcanoes. Jurassic sediments cover transgressively Permian volcanics forming several confined aquifers within a subsided, triangle shaped block. The aquifers are saturated with groundwater derived from the Khar Argalantyn Nuruu Mts. To the northwest and on the east this block is bordered by sealed faults. The significant recent seismic activity occurring in the area is related to Cenozoic faults as a response to the collision of the Indian and Eurasian continental plates. The mud volcanoes originated probably as a result of the Gobi-Altay Earthquake in 1957. The earthquake of magnitude 8.3 generated new fractures or reactivated existing fractures. The impulse of the earthquake exceeding the thixotropy of fine-grained sediments initiated the rise of the mud volcanoes. The recent equilibrium of pressure condition in the area is labile. Earthquakes or increase in piezometric level of groundwater caused by heavy rainfalls can trigger activity of the mud volcanoes. A high content of smectites in sediments and loss of binding of clay particles due to soluble salts support mud outflows during such starting events.
Keywords: mud volcano; liquefaction; thixotropy; earthquake; Gobi Altay; Mongolia